Structural and Functional Insights Into Skl and Pal Endolysins, Two Cysteine-Amidases With Anti-pneumococcal Activity. Dithiothreitol (DTT) Effect on Lytic Activity - Gallego-Páramo, Cristina; Hernández-Ortiz, Noelia; Buey, Rubén M.; Rico-Lastres, Palma; García, Guadalupe; Díaz, J. Fernando; García, Pedro; Menéndez, Margarita (Frontiers in Microbiology, 2021)
We have structurally and functionally characterized Skl and Pal endolysins, the latter being the first endolysin shown to kill effectively Streptococcus pneumoniae, a leading cause of deathly diseases. We have proved that Skl and Pal are cysteine-amidases whose catalytic domains, from CHAP and Amidase_5 families, respectively, share an 3β6 fold with papain-like topology. Catalytic triads are identified (for the first time in Amidase_5 family), and residues relevant for substrate binding and catalysis inferred from in silico models, including a calcium-binding site accounting for Skl dependence on this cation for activity. Both endolysins contain a choline-binding domain (CBD) with a β-solenoid fold (homology modeled) and six conserved choline-binding loci whose saturation induced dimerization. Remarkably, Pal and Skl dimers display a common overall architecture, preserved in choline-bound dimers of pneumococcal lysins with other catalytic domains and bond specificities, as disclosed using small angle X-ray scattering (SAXS). Additionally, Skl is proved to be an efficient anti-pneumococcal agent that kills multi-resistant strains and clinical emergent-serotype isolates. Interestingly, Skl and Pal time-courses of pneumococcal lysis were sigmoidal, which might denote a limited access of both endolysins to target bonds at first stages of lysis. Furthermore, their DTT-mediated activation, of relevance for other cysteine-peptidases, cannot be solely ascribed to reversal of catalytic-cysteine oxidation.